2005
DOI: 10.1371/journal.pbio.0030351
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Regulates Transcription in the Zebrafish Circadian Clock

Abstract: It has been well-documented that temperature influences key aspects of the circadian clock. Temperature cycles entrain the clock, while the period length of the circadian cycle is adjusted so that it remains relatively constant over a wide range of temperatures (temperature compensation). In vertebrates, the molecular basis of these properties is poorly understood. Here, using the zebrafish as an ectothermic model, we demonstrate first that in the absence of light, exposure of embryos and primary cell lines to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
151
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(176 citation statements)
references
References 43 publications
18
151
1
6
Order By: Relevance
“…To elucidate how the intracellular oscillators physiologically interact with the external temperature cycles, entrainment kinetics were carefully studied by applying various non-24-hour cycles (T cycles; 9, 10). On the other hand, to study molecular events that linked with external temperature signals, temperature-dependent processes such as transcription, translation, RNA processing, protein stability, and protein-protein interactions were analyzed in several model organisms (11)(12)(13).…”
mentioning
confidence: 99%
“…To elucidate how the intracellular oscillators physiologically interact with the external temperature cycles, entrainment kinetics were carefully studied by applying various non-24-hour cycles (T cycles; 9, 10). On the other hand, to study molecular events that linked with external temperature signals, temperature-dependent processes such as transcription, translation, RNA processing, protein stability, and protein-protein interactions were analyzed in several model organisms (11)(12)(13).…”
mentioning
confidence: 99%
“…Similar to behavioral rhythms in Drosophila, RNA rhythms in fish were synchronized even if the amplitude of the thermocycle was as low as 2°C (Wheeler et al 1993;Lahiri et al 2005). Moreover, it was shown that the abundance and phosphorylation status of zebra fish Clk1 is different at constant low (20°C) versus high (30°C) temperatures during LD cycles (Lahiri et al 2005). Although this does not directly address the question of whether these differences at the protein level contribute to temperature entrainment, it does suggest that posttranscriptional regulation also contributes to thermal entrainment in vertebrates.…”
Section: Role Of Transcriptional and Posttranscriptional Mechanismsmentioning
confidence: 82%
“…Transcriptional rhythms of potential core clock genes could also be induced by temperature cycles in zebra fish cells and larvae (Lahiri et al 2005). Similar to behavioral rhythms in Drosophila, RNA rhythms in fish were synchronized even if the amplitude of the thermocycle was as low as 2°C (Wheeler et al 1993;Lahiri et al 2005).…”
Section: Role Of Transcriptional and Posttranscriptional Mechanismsmentioning
confidence: 87%
See 2 more Smart Citations